DEVELOPMENT OF INFORMATION SUPPORT FOR THE INVESTMENT PROJECT CONTROLLING STAGES - G. Khudaiberdina; Y. Rudneva (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the practical aspects of the organization of the stages ofplanning and control in the implementation of investment projects in an industrial enterprise. Schemes of information support of these stages are detailed in connection with the operations of controllers. For the purpose of improving monitoring over the course of project implementation, a system of benchmarks for the implementation of the project is proposed, criteria for the materiality of deviations from benchmarks for the implementation of investment projects are defined, and possible management decisions are formulated if deviations of benchmarks arise during the implementation of investment projects.